Aspects of Illness and Death among Roma-Have They Changed after More than Two Hundred Years? - Kozubik, Michal; van Dijk, Jitse P; Filakovska Bobakova, Daniela (International journal of environmental research and public health, 2019)
Augustini studied Roma and published reports in 1775-1776 on their illnesses and death. Our intention was to compare the features of these two topics described by him in the late 18th century with those in the present time. We studied Augustini's work on illnesses and death in the past. The present qualitative study was conducted in 2012-2013 in the same geographical area in which Augustini lived and worked more than two hundred years ago, i.e., the Tatra Region in Slovakia; our findings were evaluated in 2017-2018. We carried out semi-structured interviews with more than 70 informants and organised two sessions of focus groups. Data were analysed using content analysis (Augustini) and an open coding process. Our findings suggest that illnesses in Roma are treated differently nowadays compared with 1775-1776. For example, the traditional forms of healing have completely disappeared in the area of investigation. We did not observe any differences in dying and death perceptions between the past and nowadays. Although data and knowledge on health disparities and related mechanisms exist, and much more about perceptions of Roma regarding illnesses is now known compared with 1775-1776, so far, this knowledge has not helped to design effective interventions to overcome them. Substandard living conditions in marginalised Roma communities have not significantly improved since 1775-1776, which may contribute to their higher morbidity and mortality also nowadays. Political and social consensus should lead to a comprehensive vision for enhancing the social situation and living conditions in segregated settlements, especially providing housing for the poorest classes and overcoming health disparities.
Keywords: Qualitative Research; 2012; Female; Mortality; illnesses; ženské pohlaví; nemoc; Slovakia; lidé; 1775; Disease; mortalita; death; Male; Romové; Roma; Slovenská republika; mužské pohlaví; kvalitativní výzkum; Humans